Tomato Value Chain in Kebbi State: Issues, Challenges and Strategies - Danmaigoro, Aliyu; Aliyu, Aminu; Aliyu, Abdulrahman (Indonesian Journal of Advanced Research, 2024)
In order to support the growth of tomato production and processing in the Kebbi State, an assessment of the tomato value chain was conducted. Approximately 2.3 million metric tons of fresh tomatoes are produced annually in Nigeria, but over half of them are wasted because of inadequate transportation, storage, and processing facilities. Because of this, it is critical to create plans for the tomato value chain's development. A critical analysis of the body of existing research and a schedule of interviews with important participants in the value chain, including producers, intermediary traders, retailers, and input suppliers, were the methods used for this study. Despite the great output of fresh tomatoes, the study also showed that Kebbi State is still not a major exporter of processed or fresh tomato products. It was discovered that this was caused by a lack of high-quality seed supplies, inadequate storage facilities, subpar disease and insect control, and subpar processing facilities. In order to overcome the obstacles, policies should support Small and Medium Enterprises (SMEs) throughout the value chain; input supplies should be improved; farmers should be organized into cooperatives to launch creative funding mechanisms for them; processors should be placed in clusters; marketing strategies should be improved, including guaranteeing prices for fresh tomato products; technologies for processing and storage should be developed; farmers should adopt Good Agricultural Practices (GAP); and a strong National Commodity Association or Network should be established.